1987
DOI: 10.1128/aac.31.5.799
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the novel cephalosporin cefepime (BMY-28142) in rats and monkeys

Abstract: The disposition of the novel cephalosporin cefepime (BMY-28142) was characterized for intravenous administration of single doses to rats and cynomolgus monkeys, the species used most extensively for safety evaluation of the compound. Serial blood samples were collected from individual animals, and plasma was analyzed for intact cefepime by a high-pressure liquid chromatography-UV method. Assay results were evaluated by compartmental and noncompartmental methods to characterize pharmacokinetics for each species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…36,1992 on May 7, 2018 by guest http://aac.asm.org/ Downloaded from 11) were also compared with respect to dose levels in a manner analogous to that described above for the initial dose on day 1. The results for day 11 closely paralleled those noted above for day 1. No significant differences with respect to the dose in the analyses of tl2, MRT, CLr, CLR, VS., the dose-normalized Cm., and AUCO, were observed.…”
Section: Resultssupporting
confidence: 77%
“…36,1992 on May 7, 2018 by guest http://aac.asm.org/ Downloaded from 11) were also compared with respect to dose levels in a manner analogous to that described above for the initial dose on day 1. The results for day 11 closely paralleled those noted above for day 1. No significant differences with respect to the dose in the analyses of tl2, MRT, CLr, CLR, VS., the dose-normalized Cm., and AUCO, were observed.…”
Section: Resultssupporting
confidence: 77%
“…Pharmacokinetic studies with monkeys indicated that cefepime exhibits linear pharmacokinetics and that glomerular filtration is the major route of elimination of this cephalosporin (7). The results of the present study indicate that the concentrations of cefepime in plasma increased with increasing dose in a dose-proportional manner and doseindependent parameters such as mean residence time, CLT, and CLR remained independent of dose.…”
Section: Discussionsupporting
confidence: 60%
“…The findings of these studies suggest that when administered by intravenous infusion, cefepime is as safe as other commercially available cephalosporins. The pharmacokinetics in rats and monkeys have been extensively characterized (2,7). The present phase I study was designed to evaluate the safety, tolerance, and pharmacokinetics of cefepime in healthy male volunteers.…”
mentioning
confidence: 99%
“…Cefoperazone was included because it has broad-spectrum activity against intestinal anaerobic bacteria and is excreted predominantly in the bile (6); ceftriaxone was included because it is also excreted into the bile (23), but it lacks broad antianaerobe activity. Ceftazidime was studied because it lacks broad antianaerobe activity and, unlike cefoperazone and ceftriaxone, is mainly excreted by the kidney (22); and cefepime was studied because, like ceftazidime, it is mainly excreted by the kidney (9), but its antibacterial spectrum includes gram-positive * Corresponding author. cocci such as Staphylococcus aureus (13,14,25).…”
mentioning
confidence: 99%